Eosinophil-derived chemokine (hCCL15/23, mCCL6) interacts with CCR1 to promote eosinophilic airway inflammation - Xufei Du; Fei Li; Chao Zhang; Na Li; Huaqiong Huang; Zhehua Shao; Min Zhang; Xueqin Zhan; Yicheng He; Zhenyu Ju; Wen Li; Zhihua Chen; et al. (Signal Transduction and Targeted Therapy, 2021)
Abstract Eosinophils are terminally differentiated cells derived from hematopoietic stem cells (HSCs) in the bone marrow. Several studies have confirmed the effective roles of eosinophils in asthmatic airway pathogenesis. However, their regulatory functions have not been well elucidated. Here, increased C-C chemokine ligand 6 (CCL6) in asthmatic mice and the human orthologs CCL15 and CCL23 that are highly expressed in asthma patients are described, which are mainly derived from eosinophils. Using Ccl6 knockout mice, further studies revealed CCL6-dependent allergic airway inflammation and committed eosinophilia in the bone marrow following ovalbumin (OVA) challenge and identified a CCL6-CCR1 regulatory axis in hematopoietic stem cells (HSCs). Eosinophil differentiation and airway inflammation were remarkably decreased by the specific CCR1 antagonist BX471. Thus, the study identifies that the CCL6-CCR1 axis is involved in the crosstalk between eosinophils and HSCs during the development of allergic airway inflammation, which also reveals a potential therapeutic strategy for targeting G protein-coupled receptors (GPCRs) for future clinical treatment of asthma.